Compacity in narrow limit tower spaces - Liviu C. Florescu (International Journal of Mathematics and Mathematical Sciences)
We introduce a limit tower structure on the space of all bounded Radon measures on a completely regular space and we extend the Prohorov's theorem of narrow compactness. In the particular case of Polish spaces, we give a sequential version of this extension.